I survived the attacks of September 11, 2001 - Ball, Georgia; Egbert, Corey, 1988-; Tarshis, Lauren (New York : Graphix, 2021)
When Lucas decides to skip school because he wants to discuss football with a firefighter friend of his father, he finds himself caught up in the terrorist attacks on New York City.
Based on: I survived the attacks of September 11, 2001 / Lauren Tarshis.
Includes bibliographical references.
3.8
3-6
GN570L
Keywords: September 11 Terrorist Attacks, 2001 -- Comic books, strips, etc -- Juvenile fiction; Terrorism -- New York (State) -- New York -- Comic books, strips, etc -- Juvenile fiction; Adventure stories; September 11 Terrorist Attacks, 2001 -- Fiction; Terrorism -- Fiction; New York (N.Y.) -- Fiction; Adventure and adventurers -- Fiction; Cartoons and comics; Action and adventure comics; Historical comics; Graphic novel adaptations; Graphic novels; Comics (Graphic works)